Weaving the threads of international criminal justice: The double dialogicity of law and politics in the ICC al-Mahdi case. (December 2021) - D'hondt, Sigurd; Dupret, Baudouin; Bens, Jonas
Abstract: In this paper, we examine the international criminal trial of Ahmad al-Faqi al-Mahdi, a Malian Islamist who appeared before the International Criminal Court (ICC) in The Hague, charged with the destruction of Islamic shrines during the 2012 jihadist occupation of Timbuktu. Our objective is to analyze the al-Mahdi case as a dialogical network (the destructions occurred in the context of an asynchronous, translocal, press-mediated exchange between jihadists and the international community) and as an event unfolding at a dialogical site (when the commander responsible for the destructions was referred to the ICC four years later). These two dialogical orders exist largely independent of each other but are at crucial points also partly entangled. We conclude by pointing out the relevance of this 'doubly dialogical' approach to the broader field of sociolegal studies of international criminal justice.